A Collaborative Multimedia Project Model for Online Graduate Students Supported by On-Campus Undergraduate Students. (January 2021) - Goode, Jennifer
This descriptive narrative depicts an academic program that deploys a collaborative project model for delivering concurrent multimedia courses at the undergraduate and graduate levels. Applying this model, online master's students who are studying the management of technical communication activities remotely manage teams of on-campus undergraduate students who are studying multimedia production skills. The author piloted the collaborative project model during a recent academic term. Student response to the format was overwhelmingly positive from both graduates and undergraduates, and the resulting projects were of exceptional quality and well received by their respective clients.